Private- Cooperatives Synergy in the Face of Agricultural Policy Changes: Moral Hazard Behavior Ameliorated? An Experience from Coffee Cooperatives in Southern Highlands, Tanzania - Lumenyela, Rogers A.; Dimosso, Provident; Chusi, Tafuteni (Journal of Economics and Behavioral Studies, 2023)
The private sector is essential for improving the coffee sector by supporting farmers through cooperatives and groups. The study objective is to assess the impact of policy changes on moral hazard and private-farmers investment synergy. The present study used data collected from coffee farmers and cooperatives in Mbeya, Songwe and Ruvuma in Tanzania. Analyses were achieved by using descriptive statistics and difference-in-difference (DiD) at both the farm level and cooperative level. The results indicate that the 2017/2018 government policy changes ameliorated moral hazard and free-riding behaviors among farmers, owing to repay loans. Cooperatives with contractual arrangements with private investors suffered from moral hazards attributable to policy changes whereby the decline in the coffee collection was 33,040 kg (with an average treatment effect on the treated (ATT)) of coffee parchment, whereas, at the farmers’ level, farmers reduced the collection of coffee with an ATT of 24.6 kg. In addition, because of these changes, some central pulse units were found to be non-functional, while others were under-utilized. In this regard, such moral hazard behavior among coffee farmers destabilized cooperatives, as well as the existing synergy between private investors and cooperatives. It is recommended that before policy or any institutional change, it is important to consider strategies and paths to reduce the moral hazard and free-riding behaviors of any stakeholder to improve market efficiency. For the coffee sector, this would include farmers collecting coffee from member cooperatives only. The government must consider having an effective institutional/policy change mechanism, in particular having a preparatory stage for policy change, to ensure that all contracts that have to be affected by such changes are reinforced properly to reduce unnecessary losses for any actor in the value chain. The government can facilitate or mediate disputes related to investments in agriculture, provide administrative support, and help negotiate compensation.